GREEN MARKETING AND ECO-LABEL IN SUSTAINABLE SKINCARE: HOW ENVIRONMENTAL AWARENESS SHAPES DECISION - Sari, Fadia Paloma; Sari, Puspa Novita (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
This study examines the effect of green marketing and eco-labels on purchase decisions by considering environmental awareness as a mediating variable using the S-O-R theory (Stimulus-Organism-Response). A sample of 227 The Body Shop at Shopee consumers was selected using purposive sampling. Data analysis using the Structural Equation Model (SEM) method based on Partial Least Squares (PLS). The analysis results show that green marketing and eco-label significantly affect environmental awareness and purchase decisions; environmental awareness significantly affects purchase decisions and mediates the relationship between green marketing and purchase decisions; and eco-label mediates the relationship between purchase decisions. Shows that consumers with higher environmental awareness tend to choose environmentally friendly products. The implications of this study emphasize the importance of green marketing and eco-labeling in shaping environmental awareness to form consumer purchasing decisions. This study has limitations in scope, so the results cannot be generalized. Therefore, future research is recommended to expand the scope of the study and use a qualitative approach to gain a deeper understanding.